Preparation method and application of cerium-cobalt composite oxide electrocatalyst

By preparing cerium-cobalt composite oxide electrocatalyst, the problem of high overpotential in electrocatalytic oxidation of glycerol is solved, low voltage and high efficiency catalysis are achieved, with high selectivity and good cycling performance, and cost is reduced.

CN119640320AActive Publication Date: 2025-03-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510124407.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-18
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

The prior art requires high overpotentials in electrocatalytic oxidation of glycerol, resulting in large electricity consumption, and high cost of precious metal catalysts and are prone to toxicity and inactivation.

Method used

Using the preparation method of cerium-cobalt composite oxide electrocatalyst, a cerium-cobalt composite oxide electrocatalyst is prepared by stirring soluble cerium salt, soluble cobalt salt and urea in water to form a mixed liquid, and react with a carbon fiber substrate at high temperature, and then drying and calcining.

Benefits of technology

During the glycerol oxidation process, the catalyst only needs a voltage of 1.38V to achieve a starting current density of 10mA·cm-2, which reduces the overpotential, has high selectivity and Faraday efficiency, and has good cycling performance and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640320A_ABST
    Figure CN119640320A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a cerium-cobalt composite oxide electrocatalyst, which comprises the following steps: soluble cerium salt, soluble cobalt salt and urea are added into water and stirred to form a mixed solution, the cerium ion concentration is 4-95 mmol / L, the cobalt ion concentration is 40-60 mmol / L, and the molar ratio of the total metal amount of the soluble cobalt salt and the soluble cerium salt to the urea is (0.01-0.5): 1; adding the mixed solution and a carbon fiber substrate into a closed container, keeping at 100-160 DEG C for 2-24 hours, and cooling to room temperature to obtain a carbon fiber substrate loaded with a catalyst precursor; the carbon fiber substrate loaded with the catalyst precursor is dried and calcined, the calcination temperature is 300-500 DEG C, the calcination time is 1-4 h, the heating rate is 1-5 DEG C / min, and the cerium-cobalt composite oxide electrocatalyst is obtained. The synthesis method is simple, low in cost and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and relates to a method for preparing a cerium-cobalt composite oxide electrocatalyst and application of the prepared electrocatalyst in glycerol oxidation. Background Art

[0002] Glycerol is a C3 platform molecule and a major byproduct of biodiesel production. Selective oxidation of glycerol can produce many high value-added products, including dihydroxyacetone, glyceric acid, tartaric acid, meta-oxalic acid, glycolic acid, and formic acid. Unlike the traditional thermal catalytic glycerol oxidation reaction (GOR), electrocatalytic GOR is a promising approach that can be carried out at low cost and high efficiency at moderate temperatures and atmospheric pressure. In addition, by controlling the composition and structure of the catalyst and reaction variables such as electrode potential, electrolyte pH, glycerol concentration, reaction temperature, and reaction time, the product generation path can be well controlled and the selectivity of product generation can be improved. Its only drawback is that the reaction often requires a very high overpotential, and large-scale production requires a lot of electricity. However, through the rational design of the catalyst structure, highly active and highly selective catalysts with specific surface composition and morphology can be synthesized to reduce the overpotential of the reaction.

[0003] The key to the selective oxidation of glycerol is the design and development of efficient catalysts. In order to explore cleaner and more efficient methods for the oxidation and value-added conversion of glycerol, many chemical researchers have done a lot of research and attempts. Under typical electrolysis conditions, precious metal (Au, Pt, Pd)-based catalysts show excellent adsorption capacity for glycerol. In a relatively low potential environment, it can guide the electro-oxidation reaction of glycerol and greatly improve the selectivity of the reaction. In particular, in the reaction of selective preparation of glycolic acid by electrocatalytic oxidation of glycerol, precious metals can generate such high value-added products with high selectivity. However, precious metals are not only expensive, but also can usually only produce high-value products at low potentials and relatively small currents. They are easily over-oxidized to carbon dioxide at high potentials and are easily poisoned and inactivated by highly coordinated species produced during the oxidation of glycerol.

[0004] Therefore, the development of resource-abundant, low-cost, high-performance, and stable electrocatalysts is of great significance for efficient electro-oxidation of glycerol to C2 products. Summary of the invention

[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a preparation method and application of a cerium-cobalt composite oxide electrocatalyst.

[0006] The present invention provides a method for preparing a cerium-cobalt composite oxide electrocatalyst, which comprises the following steps:

[0007] Adding soluble cerium salt, soluble cobalt salt and urea into water and stirring to form a mixed solution, wherein the cerium ion concentration is 4-95 mmol / L, the cobalt ion concentration is 40-60 mmol / L, and the molar ratio of the total amount of metal of the soluble cobalt salt and the soluble cerium salt to urea is (0.01-0.5):1;

[0008] The mixed solution and the carbon fiber substrate are added into a sealed container, maintained at 100 to 160° C. for 2 to 24 hours, and cooled to room temperature to obtain a carbon fiber substrate loaded with a catalyst precursor;

[0009] The carbon fiber substrate carrying the catalyst precursor is dried and calcined at a temperature of 300 to 500° C., a calcination time of 1 to 4 hours, and a heating rate of 1 to 5° C. / min to obtain the cerium-cobalt composite oxide electrocatalyst.

[0010] The present invention also provides application of the cerium-cobalt composite oxide electrocatalyst obtained by the method in electrocatalytic glycerol oxidation.

[0011] Compared with the prior art, the present invention has the following beneficial effects:

[0012] (1) The electrocatalyst preparation method proposed in the present invention is an in-situ growth method, which can prepare a composite electrocatalyst with uniform nanofiber morphology. The synthesis method is simple and suitable for large-scale production. It solves the problem that the traditional hydrothermal method is difficult to grow cerium metal on a carbon fiber substrate. The use of cobalt metal can synergistically promote directional growth on the surface of carbon paper fibers.

[0013] (2) The carbon fiber substrate has excellent electrical conductivity. In the electrocatalytic process, good electrical conductivity can ensure that electrons can be efficiently transferred between the electrode (carbon fiber substrate) and the electrocatalyst, reducing energy loss during electron transfer and making it more stable and efficient.

[0014] (3) Rare earth cerium oxide has a unique 4f electronic structure. When combined with transition metal oxides, it can regulate the d-band center, improve the adsorption of catalysts and substrates and the desorption of products in catalytic reactions, increase the electron transfer rate, and improve the electrolysis efficiency.

[0015] (4) The catalyst exhibits excellent electrocatalytic activity towards glycerol. During the glycerol oxidation process, the catalyst only requires a voltage of 1.38 V (vs. RHE) to reach 10 mA cm -2 The starting current density is 100 mV lower than that of the anodic oxygen evolution reaction; and the electrolysis products are analyzed by chronoamperometry, and the catalyst has high selectivity and Faraday efficiency for C2 products.

[0016] (5) The catalyst also has excellent recycling performance. After the catalyst was operated at a potential of 1.4 V (vs. RHE) for 10 h and recycled three times, its catalytic performance did not show obvious attenuation and had good stability.

[0017] (6) Compared with the reported selectivity of precious metal catalysts such as AuCu alloy in the electrocatalytic reaction of glycerol to glycolic acid, the catalyst prepared in the present invention not only shows higher selectivity in this reaction, but also has greatly reduced cost, with significant advantages in terms of economy and performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope image of the cerium-cobalt composite oxide electrocatalyst obtained in Example 1 of the present invention.

[0019] Figure 2 This is a scanning electron microscope image of the cerium-cobalt composite oxide electrocatalyst obtained in Example 2 of the present invention.

[0020] Figure 3 This is a scanning electron microscope image of the cerium-cobalt composite oxide electrocatalyst obtained in Example 3 of the present invention.

[0021] Figure 4 This is a scanning electron microscope image of the cobalt oxide electrocatalyst obtained in Comparative Example 1 of the present invention.

[0022] Figure 5 This is the XRD crystal phase diagram of the cerium-cobalt composite oxide electrocatalyst of Example 1 of the present invention.

[0023] Figure 6 This is the XRD crystal phase diagram of the cobalt oxide electrocatalyst obtained in Comparative Example 1 of the present invention.

[0024] Figure 7 This is a scanning electron microscope image of the gadolinium cobalt composite oxide electrocatalyst obtained in Comparative Example 2 of the present invention.

[0025] Figure 8 This is the LSV curve of the cerium-cobalt composite oxide electrocatalyst obtained in Example 1 of the present invention applied to electrocatalytic glycerol oxidation.

[0026] Fig. 9 This is a graph showing the cycle performance of the cerium-cobalt composite oxide electrocatalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] The present invention provides a method for preparing a cerium-cobalt composite oxide electrocatalyst, which comprises the following steps:

[0029] S01: Add soluble cerium salt, soluble cobalt salt and urea into water and stir to form a mixed solution, wherein the cerium ion concentration is 4-95 mmol / L, the cobalt ion concentration is 40-60 mmol / L, and the molar ratio of the total metal amount of the soluble cobalt salt and the soluble cerium salt to urea is (0.01-0.5):1.

[0030] S02: adding the mixed solution and the carbon fiber substrate into a closed container, maintaining the mixture at 100 to 160° C. for 2 to 24 hours, and cooling to room temperature to obtain a carbon fiber substrate loaded with a catalyst precursor;

[0031] S03: drying and calcining the carbon fiber substrate loaded with the catalyst precursor at a calcination temperature of 300-500° C., a calcination time of 1-4 hours, and a heating rate of 1-5° C. / min to obtain the cerium-cobalt composite oxide electrocatalyst.

[0032] Specifically, in step S01, the soluble cerium salt is cerium chloride or cerium nitrate, and the soluble cobalt salt is cobalt chloride or cobalt nitrate, which may or may not contain crystal water. Preferably, the concentration of cerium ions is 20 to 55 mmol / L. The molar ratio of the total amount of metal of the soluble cobalt salt and the soluble cerium salt to urea is (0.01 to 0.5):1, for example, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.3, 0.4, 0.5, etc. Preferably, the molar ratio of the total amount of metal of the soluble cobalt salt and the soluble cerium salt to urea is (0.05 to 0.4):1.

[0033] In step S02, the carbon fiber substrate can be a carbon fiber substrate such as carbon cloth and carbon paper. Preferably, it is carbon fiber paper. The carbon fiber substrate is cut into the required size, ultrasonically cleaned in ethanol and water for 10 minutes, and impurities on the surface of the carbon fiber substrate are removed. After being placed in an oven at 80°C for drying, it is calcined in an air atmosphere in a muffle furnace for 2 hours to obtain a pretreated carbon paper fiber substrate; the calcination temperature of the carbon fiber substrate is 200-400°C, such as 200°C, 250°C, 300°C, 350°C or 400°C, etc., preferably 250°C-300°C. The calcination time is 1-4h, such as 1h, 2h, 3h, 4h, etc., preferably 1h-2h.

[0034] Specifically, the mixed solution is transferred to a sealed container, the pretreated substrate is added, and the mixture is heated to 120-140° C. for reaction for 6-12 hours to obtain a carbon fiber substrate loaded with a catalyst precursor; the sealed container may be a hydrothermal autoclave.

[0035] In step S03, specifically, the carbon fiber substrate carrying the catalyst precursor is calcined at 300° C. to 500° C. in an air atmosphere to obtain the cerium-cobalt composite oxide electrocatalyst.

[0036] The calcination temperature is 300-500°C, for example 300°C, 350°C, 400°C, 450°C, 500°C, etc. Preferably, the calcination temperature is 350-400°C, and the calcination time is 1h-4h, for example 1h, 2h, 3h, 4h, etc., preferably 1h-2h.

[0037] The embodiment of the present invention also provides the use of the cerium-cobalt composite oxide electrocatalyst prepared by the above method in the electrocatalytic oxidation of glycerol.

[0038] Specifically, the prepared cerium-cobalt composite oxide electrocatalyst was used as a working electrode, a platinum sheet was used as a counter electrode, and Ag / AgCl was used as a reference electrode to assemble a three-electrode system for glycerol oxidation.

[0039] Optionally, the electrolyte selected in the electrocatalytic oxidation process of glycerol is an alkaline solution of glycerol, which can be a mixed solution of glycerol and potassium hydroxide, wherein the concentration of glycerol is 0.1-2 mol / L, such as 0.1, 0.2, 0.3, 0.5, 0.6, 0.8, 1, 1.5 or 2 mol / L, and preferably 0.3-0.5 mol / L. The concentration of potassium hydroxide is 1 mol / L.

[0040] The following specific examples illustrate the preparation method of the cerium-cobalt composite oxide electrocatalyst and its application in the electrocatalytic oxidation of glycerol. The self-supporting electrodes in the following examples can be directly prepared according to existing methods, and of course, can also be directly purchased from the market, but are not limited thereto.

[0041] Example 1 :

[0042] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0043] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0044] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0045] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0046] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0047] Electrocatalytic glycerol oxidation:

[0048] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 42%, the selectivity for glyceric acid was 13%, and the selectivity for formic acid was 45%.

[0049] Example 2 :

[0050] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0051] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0052] Weigh 0.08mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0053] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0054] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0055] Electrocatalytic glycerol oxidation:

[0056] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 38%, the selectivity for glyceric acid was 7%, and the selectivity for formic acid was 55%.

[0057] Example 3 :

[0058] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0059] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0060] Weigh 1.6mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0061] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0062] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0063] Electrocatalytic glycerol oxidation:

[0064] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 35%, the selectivity for glyceric acid was 7%, and the selectivity for formic acid was 58%.

[0065] Example 4 :

[0066] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0067] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0068] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0069] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 140°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0070] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0071] Electrocatalytic glycerol oxidation:

[0072] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 31%, the selectivity for glyceric acid was 25%, and the selectivity for formic acid was 44%.

[0073] Example 5 :

[0074] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0075] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0076] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0077] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 4 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0078] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0079] Electrocatalytic glycerol oxidation:

[0080] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 33%, the selectivity for glyceric acid was 20%, and the selectivity for formic acid was 47%.

[0081] Example 6 :

[0082] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0083] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0084] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0085] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0086] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 400°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0087] Electrocatalytic glycerol oxidation:

[0088] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 35%, the selectivity for glyceric acid was 25%, and the selectivity for formic acid was 40%.

[0089] Example 7 :

[0090] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0091] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0092] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0093] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0094] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0095] Electrocatalytic glycerol oxidation:

[0096] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.1 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 37%, the selectivity for glyceric acid was 8%, and the selectivity for formic acid was 55%.

[0097] Example 8 :

[0098] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0099] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0100] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0101] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0102] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0103] Electrocatalytic glycerol oxidation:

[0104] A three-electrode system was used to evaluate the reaction performance of the prepared cerium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as a working electrode, a platinum sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.1 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.3 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 39%, the selectivity for glyceric acid was 20%, and the selectivity for formic acid was 41%.

[0105] Comparative Example 1 :

[0106] Preparation of cobalt oxide electrocatalysts:

[0107] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0108] Weigh 0.8 mmol CoCl2·6H2O into a 100 mL beaker, add 0.5 g urea and 17 mL water, and stir to form a transparent pink solution;

[0109] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0110] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cobalt oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0111] Electrocatalytic glycerol oxidation:

[0112] A three-electrode system was used to evaluate the reaction performance of the prepared cobalt oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was measured by chronoamperometry (1.4 V), and the charge was 100C. The product was detected by liquid chromatography, and the selectivity for glycolic acid was 20%, the selectivity for glyceric acid was 27%, and the selectivity for formic acid was 53%.

[0113] Comparative Example 2 :

[0114] Preparation of Gadolinium Cobalt Composite Oxide Electrocatalyst:

[0115] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0116] Weigh 0.8mmol GdCl3 and 0.8mmol CoCl2·6H2O in a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0117] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0118] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a gadolinium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0119] Electrocatalytic glycerol oxidation:

[0120] A three-electrode system was used to evaluate the reaction performance of the prepared gadolinium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as a working electrode, a platinum sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity of glycolic acid was 30%, the selectivity of glyceric acid was 20%, and the selectivity of formic acid was 50%.

[0121] Comparative Example 3 :

[0122] Preparation of NdCo composite oxide electrocatalyst:

[0123] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0124] Weigh 0.8mmol NdCl3 and 0.8mmol CoCl2·6H2O in a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0125] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0126] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a neodymium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0127] Electrocatalytic glycerol oxidation:

[0128] A three-electrode system was used to evaluate the reaction performance of the prepared neodymium cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as a working electrode, a platinum sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 10%, the selectivity for glyceric acid was 28%, and the selectivity for formic acid was 62%.

[0129] Comparative Example 4 :

[0130] Preparation of nickel-cobalt composite oxide electrocatalyst:

[0131] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0132] Weigh 0.8mmol NiCl2 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0133] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0134] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a nickel-cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0135] Electrocatalytic glycerol oxidation:

[0136] A three-electrode system was used to evaluate the reaction performance of the prepared nickel-cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as a working electrode, a platinum sheet was used as a counter electrode, Ag / AgCl was used as a reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 5%, the selectivity for glyceric acid was 10%, and the selectivity for formic acid was 85%.

[0137] Comparative Example 4 :

[0138] Preparation of copper-cobalt composite oxide electrocatalysts:

[0139] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0140] Weigh 0.8mmol CuCl2 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0141] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0142] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a copper-cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0143] Electrocatalytic glycerol oxidation:

[0144] A three-electrode system was used to evaluate the reaction performance of the prepared copper-cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, a platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was a 1 mol / L potassium hydroxide solution of 0.3 mol / L glycerol. At room temperature, the selective oxidation performance of the catalyst was tested by chronoamperometry (1.4 V), the charge was 100C, and the product was detected by liquid chromatography, and the selectivity for glycolic acid was 5%, the selectivity for glyceric acid was 10%, and the selectivity for formic acid was 85%.

[0145] Comparative Example 7:

[0146] Preparation of cerium-cobalt composite oxide electrocatalyst:

[0147] The carbon paper was cut into 1×2 cm size, ultrasonically cleaned in ethanol and water for 10 min to remove impurities on the surface of the carbon paper fiber, dried in an oven at 80°C, and calcined in a muffle furnace at 250°C for 2 h in air atmosphere to obtain a pretreated carbon fiber substrate;

[0148] Weigh 0.8mmol CeCl3 and 0.8mmol CoCl2·6H2O into a 100mL beaker, add 0.5g urea and 17mL water, and stir to form a transparent pink solution;

[0149] The above uniform transparent solution was transferred to a 25 mL polytetrafluoroethylene-lined stainless steel high-pressure hydrothermal autoclave, and the pretreated carbon fiber paper was added. The solution was placed in an oven at 120°C for 6 hours. After the reaction was completed, the autoclave was left to cool to room temperature.

[0150] The carbon paper with the precursor grown on it was taken out, rinsed repeatedly with deionized water and ethanol, placed in an oven at 80°C for 6 hours, and then calcined in a muffle furnace. The calcination temperature was set to 350°C, the calcination time was 2 hours, and the heating rate was 2.5°C / min to obtain a cerium cobalt composite oxide electrocatalyst uniformly grown on the carbon paper substrate.

[0151] Electrocatalytic glycerol oxidation:

[0152] A three-electrode system was used to evaluate the reaction performance of the prepared cerium-cobalt composite oxide electrocatalyst, that is, the prepared electrocatalyst was used as the working electrode, the platinum sheet was used as the counter electrode, Ag / AgCl was used as the reference electrode, and the electrolyte was 1 mol / L potassium hydroxide solution. At room temperature, the oxygen evolution voltage was tested by linear sweep voltammetry, and the starting voltage was 1.62V.

[0153] The morphology of cerium-cobalt composite oxide catalysts with different Ce addition amounts was studied using scanning electron microscopy. Figures 1 to 4It can be seen that cerium cobalt oxide is observed to be uniformly covered on the surface of carbon fiber to form a dense nanolayer. This structure can provide more active sites in the electrocatalytic process. By adjusting the addition ratio of CeCl3 salt in the precursor, the Ce: Co ratio is from 1:10 to 2:1. As the Ce content increases, the number of spindle-shaped nano-CeO2 in the composite oxide increases, and the area occupied on the surface of the carbon fiber also increases, indicating that by optimizing the ratio of CeO2 and Co3O4 components of the catalyst, the heterogeneous structure morphology can be regulated. When the addition ratio is further increased to 2:1, the surface of the carbon fiber is mostly spindle-shaped CeO2 structure, and Co3O4 nanowires are dotted among them. The actual Ce / Co molar ratio of the heterogeneous structure catalyst obtained by changing the amount of cerium salt was measured by ICP (Table 1), which was 0.05, 0.2, and 0.25, respectively. Further, it can be seen from the XRD data that the characteristic diffraction peak of Example 1 at 26.56° belongs to the graphite carbon structure of the carbon paper fiber, the diffraction peaks at 31.27° and 36.85° belong to the (220) and (311) crystal planes of Co3O4 (PDF#74-2120), and the diffraction peak at 28.53° belongs to the (111) crystal plane of CeO2 (PDF#89-8436), which can indicate that the crystal phase structure is a composite oxide crystal phase of CeO2 and Co3O4 ( Figure 5 ), the cobalt oxide without adding cerium salt is Co3O4 crystal phase ( Figure 6 ).

[0154] Table 1

[0155] catalyst Ce / Co ratio Example 1 0.2 Example 2 0.05 Example 3 0.25

[0156] Test the morphology of other rare earth metal and cobalt composite oxides. Figure 7 It can be seen that the growth dispersion of GdCo oxide on carbon fiber is not dense, which may be caused by the unsuitable co-growth environment of the rare earth metal and cobalt metal.

[0157] As shown in the LSV curve ( Figure 8 ), the starting potential of Example 1 for electrocatalytic glycerol oxidation is relatively low, reaching 10 mA cm at 1.38 V. -2 Current density. Fig. 9 As shown, the cerium-cobalt composite oxide catalyst obtained in Example 1 has good cycle performance and still maintains more than 40% of glycolic acid selectivity after three cycles.

[0158] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a cerium-cobalt composite oxide electrocatalyst, comprising the following steps: Soluble cerium salt, soluble cobalt salt and urea are added into water and stirred to form a mixed solution, wherein: The cerium ion concentration is 4-95 mmol / L, the cobalt ion concentration is 40-60 mmol / L, and the molar ratio of the total amount of metal of the soluble cobalt salt and the soluble cerium salt to urea is (0.01-0.5):1; The mixed solution and the carbon fiber substrate are added into a sealed container, maintained at 100 to 160° C. for 2 to 24 hours, and cooled to room temperature to obtain a carbon fiber substrate loaded with a catalyst precursor; The carbon fiber substrate loaded with the catalyst precursor is dried and calcined at a temperature of 300 to 500° C., a calcination time of 1 to 4 hours, and a heating rate of 1 to 5° C. / min to obtain the cerium-cobalt composite oxide electrocatalyst.

2. The method according to claim 1, characterized in that The concentration of the cerium ions is 20-55 mmol / L.

3. The method according to claim 1, characterized in that The molar ratio of the total amount of metals of the soluble cobalt salt and the soluble cerium salt to urea is (0.05-0.4):

1.

4. The method according to claim 1, characterized in that: The mixed solution and the carbon fiber substrate are added into a sealed container and maintained at 120-140° C. for 6-12 hours.

5. The method according to claim 1, characterized in that: The carbon fiber substrate is carbon paper or carbon cloth.

6. The method according to claim 1, characterized in that The calcination atmosphere is air.

7. The method according to claim 1, characterized in that The calcination time is 1 h to 2 h.

8. Use of the cerium-cobalt composite oxide electrocatalyst obtained by the method according to claim 1 in the electrocatalytic oxidation of glycerol.

9. A use according to claim 8, characterized in that The cerium-cobalt composite oxide electrocatalyst is used as a working electrode, a platinum sheet is used as a counter electrode, and Ag / AgCl is used as a reference electrode, and the three-electrode system is assembled for glycerol oxidation.

10. A use according to claim 8, characterized in that: The electrolyte for the electrocatalytic oxidation of glycerol is an alkaline solution of glycerol, wherein the concentration of glycerol is 0.1-2 mol / L.

Citation Information

Patent Citations

  • Preparation method of cobalt-cerium composite oxide catalyst and cobalt-cerium composite oxide catalyst

    CN105214675A

  • Method for preparing glycollic acid by electrocatalytic oxidation of glycerol

    CN117802510A